1996
DOI: 10.1111/j.1365-2729.1996.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Data‐logging: effects on practical science

Abstract: This paper describes an investigation into the processes and effects of using electronic data-logging in practical science. A pilot study of classical laboratory work in schools was compared with similar tasks performed with data-logging systems. A more detailed exploration of pupils' performance was then conducted through an extensive series of observations in a range of secondary schools. The results reinforce previous indications of the potential benefits of data-logging, but such benefits must be viewed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…This concurs with the earlier research of Rogers & Wild (1996), who observed in practical science lessons that the use of ICT and an investigative mode of working were mutually beneficial. Investigative methods of working imply a constructivist teaching approach and research has established a strong compatibility between this and ICT tasks.…”
Section: What Constitutes Successful Use Of Ict In Subject Teaching?supporting
confidence: 78%
See 1 more Smart Citation
“…This concurs with the earlier research of Rogers & Wild (1996), who observed in practical science lessons that the use of ICT and an investigative mode of working were mutually beneficial. Investigative methods of working imply a constructivist teaching approach and research has established a strong compatibility between this and ICT tasks.…”
Section: What Constitutes Successful Use Of Ict In Subject Teaching?supporting
confidence: 78%
“…The use of ICT cannot succeed on its own merits (Kennewell, 2001), but needs the actions of a teacher. Numerous studies have pointed to the importance of the teacher's role in integrating ICT into classroom teaching (Pedretti et al, 1999), the setting of parameters for learning (Scrimshaw, 1997), the definition and management of appropriate learning objectives (Rogers & Wild, 1996), supporting students with procedural strategies (Jessel, 1997;Smith, 1997) and establishing the norms and culture of the classroom (Olson, 1988).…”
Section: What Constitutes Successful Use Of Ict In Subject Teaching?mentioning
confidence: 99%
“…Newton (2000) revealed the benefits of data recorder applications in secondary schools in England. Rogers and Wild (1996) explored students' views after data recorder applications. At the end of the applications, the students who used the digital experiment tools showed improvement with time-management had enough time to interpret and discuss data without difficulty, and etc.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, datalogging frees students from taking complex measurements, tabulating data, drawing graphs by hand and executing complex calculations (Osborne & 112 K.C.D. Tan et al Hennessy, 2003) in order to tackle more conceptually demanding tasks such as the planning of experiments and, in particular, the analysis and interpretation of data (Rogers & Wild, 1994, 1996Barton, 1997b;Rogers, 1997;Newton, 2000). The benefits of datalogging depend on the quality of students' thinking about the experiment and data, for example, asking questions about data, making links with other information, making comparisons and prediction and looking for trends.…”
Section: Introductionmentioning
confidence: 99%